Over-expression of miR-210 inhibits H2O2-induced adipogenic differentiation of rat BM-MSCs - FENG Baohong, YU Yean, YAN Li, WU Jun, ZHANG Yanxia, ZHU Geli (Jichu yixue yu linchuang, 2023)
Objective To investigate the effect of miR-210 on hydrogen peroxide (H2O2)-induced adipogenic differentiation of rat bone marrow mesenchymal stem cells (BM-MSCs). Methods The SD rat BM-MSCs were isolated, cultured and identified. BM-MSCs were induced by 200 μmol/L H2O2 for 1 h to construct an adipogenic differentiation model. Adipogenic differentiation models were transfected with miR-210 mimic or inhibitor, respectively. RT-qPCR to detect the expression of miR-210; oil red O staining to detect the fat particles in the cytoplasm of cells; Western blot to detect the expression of peroxisome proliferator-activated receptor γ (PPARγ), CCAAT enhancer binding protein (C/EBPa) and Wnt/β-catenin pathway related proteins of cells. Results SD rat BM-MSCs were successfully isolated. In adipogenic differentiation model of BM-MSCs, the levels of miR-210, β-catenin, c-Myc, and cyclin D1 protein decreased, while the number of fat granules, PPARγ and C/EBPα protein levels increased; In BM-MSCs transfected with miR-210 mimic, the levels of miR-210, β-catenin, c-Myc, and cyclin D1 protein increased, while the fat granules, PPARγ, and C/EBPα protein level all decreased; The change trend of corresponding indexes in BM-MSCs transfected with miR-210 inhibitor was opposite to that in BM-MSCs transfected with miR-210 mimic. Conclusions Over-expression of miR-210 could inhibit the adipogenic differentiation of BM-MSCs induced by H2O2. This mechanism may be related to the activation of Wnt/β-catenin pathway.